Patterned Duplex Fabric Based on Genetically Modified Spidroin for Smart Wound Management. Issue 4 (28th November 2022) - Lin, Baoyang; Yuan, Liquan; Gao, Bingbing; He, Bingfang
Abstract: The treatment of diabetic wounds remains a great challenge for the medical community. Here, a smart patterned DNA double helix (duplex)‐like fabric based on genetically modified spider silk protein (PDF‐S) which is inspired by soft plant tendrils, is proposed for diabetic wound treatment. Benefiting from spider silk protein (spidroin); PDF‐S is equipped with high strength; high toughness, and excellent biocompatibility. Notably, the fabric crimped through the biomimetic DNA double‐helix‐like structure can effectively adapt to tensile impact and the maximum stretch rate reaches 1500%. A pattern‐based microfluidic channel of PDF‐S allowed wound secretion to flow spontaneously through the channel. Meanwhile; due to the optical properties of the introduced photonic crystal structure; PDF‐S is equipped with fluorescence enhancement properties; enabling PDF‐S to display color‐sensitive behavior suitable for wound monitoring and guiding clinical treatment. In addition, to enable sensitive motion monitoring, microelectronic circuits are integrated on the surface of the PDF‐S. These unique material features suggest that this study will lead to a new generation of biomimetic artificial spider silk materials for design and application in the biomedical field. Abstract : A smart patterned DNA double helix (duplex) fabric based on transgenic spider silk protein (PDF‐S) for the treatment of diabetic wounds, is proposed. PDF‐S is equipped with high strength, toughness, and conductivity, enabling sensitive motion monitoring. Meanwhile, PDF‐S has good biocompatibility, and can perform microfluidic control on wound interstitial fluid, and finally perform wound immunoassay.